Сага о шпионской любви: [роман] / И. Атаманенко - Атаманенко Игорь Григорьевич (Остросюжет, 2011)
Экземпляры: ф.1 (02.04.2012) / Инвентарный номер: 46724 / Цена: 183-38 / Авт.знак: А 92 / ГРНТИ: 17.82 / ББК: 84 (2 Рос=Рус)6